Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMA Katolik Rex Mundi Manado - Lintong, Marthinus Marcel; Kowaas, Rendi Djenever Dionisius (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
This study aims to determine how the influence of principal leadership on teacher performance at Rex Mundi Catholic High School Manado, and to determine whether or not there is an influence between principal leadership on teacher performance at Rex Mundi Catholic High School Manado. The research method used is a quantitative research method that aims to determine whether there is an influence or relationship between variable x and variable y, or vice versa. The research sample consisted of 40 respondents, obtained using saturated samples. Validity and reliability tests were carried out using IBM SPSS 25 for windows and all questionnaire items distributed were declared valid and reliable. The results of this study indicate that there is an influence between variable x and variable y with a correlation coefficient of determination of 0.415 with a percentage of 41.5%. This shows that there is an influence between the independent variable and the dependent variable with a contribution of 41.5% and the remaining 58.5% is influenced by other factors